Membaca Al-Kasyf wa Al-Bayān dalam Majma’ Al-Bayān (Analisis Narasi Proto Syi’ah dalam QS. Al-Ahzab/33: 33 dan QS. Al-Maidah/5: 67) - Muhammad Tajuddin; Bambang Sampurno; Muh. Awaluddin. A (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
The study of medieval Qur’anic exegesis needs to be developed comprehensively, especially regarding the dialectical relationships between various tafsir (exegesis) works. In this context, the researcher attempts to uncover the dialectical relationship between Tafsir al-Kashf wa al-Bayān by al-Tha‘labī and Tafsir Majma‘ al-Bayān by al-Ṭabarsī, particularly concerning proto-Shi‘i narratives and their implications for Tafsir al-Kashf wa al-Bayān. This research is descriptive qualitative in nature and is conducted through library research by collecting various literature related to the research object. The findings indicate that there are proto-Shi‘i narratives from Tafsir al-Kashf wa al-Bayān that appear in Tafsir Majma‘ al-Bayān. In this regard, al-Ṭabarsī explicitly refers to al-Tha‘labī, especially in the interpretation of Surah al-Aḥzāb (33:33) and Surah al-Mā’idah (5:67), in the context of affirming the infallibility (‘iṣmah) of Ahl al-Bayt. The effect of these quotations has been that Tafsir al-Kashf wa al-Bayān is often claimed to be a less credible tafsir even up to the present day. This research also asserts that the first Shi‘i scholar to use Tafsir al-Kashf wa al-Bayān as a reference source was al-Ṭabarsī, not Ibn Bitrīq as claimed by Walid Saleh.